Differential Association Theory Overview Against Children of Criminal Acts of Terrorism - Apriliani Kusumawati (Faculty of Sharia, State Islamic University KH. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
This paper examines children as perpetrators of criminal acts of terrorism and efforts to protect children's rights through a criminological policy approach with focus on the principles and norms of criminal law on the rights of children who are perpetrators of terrorism crimes. This normative juridical research uses a statutory, conceptual, philosophical and case approach. The analysis technique uses prescriptive analysis with logic and legal reasoning. The results of the study show that the involvement of children as perpetrators in criminal acts of terrorism is in line with the Differential Association Theory which states that criminal behavior is a learned behavior. In addition, the cause of children becoming perpetrators of acts of terrorism can also be explained through Motivation Theory. There are 2 (two) kinds of motivation, namely intrinsic motivation (internal) and extrinsic motivation (external). Efforts to protect children's human rights as perpetrators of criminal acts of terrorism through the Criminal Policy approach can be carried out with 2 (two) approaches, namely the Penal Policy or efforts to overcome crimes with criminal law and Non-Penal Policies or efforts to overcome crimes outside the criminal law.